2006
DOI: 10.1063/1.2372698
|View full text |Cite
|
Sign up to set email alerts
|

Doping and hydrogen passivation of boron in silicon nanowires synthesized by laser ablation

Abstract: Local vibrational modes of boron ͑B͒ in silicon nanowires ͑SiNWs͒ synthesized by laser ablation were observed at about 618 and 640 cm −1 by Raman scattering measurements. Boron doping was performed during the growth of SiNWs. Fano ͓Phys. Rev. 124, 1866 ͑1961͔͒ broadening was also observed in the Si optical phonon peak. These results prove that B atoms were doped in the SiNWs. Hydrogen ͑H͒ passivation of B acceptors in the SiNWs was also investigated. A broad peak was observed at around 650-680 cm −1 after hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
89
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(95 citation statements)
references
References 29 publications
5
89
0
1
Order By: Relevance
“…9,10 The results of our microRaman scattering measurements clearly showed the presence of boron ͑B͒ local vibrational peaks and Fano broadening of Si optical phonon peaks due to heavy B doping in SiNWs. 9 ESR measurements at 4.2 K showed the ESR signal of conduction electrons in phosphorus ͑P͒-doped SiNWs. 10 These results clearly proved that B and P atoms were doped in the crystalline Si core of SiNWs and were electrically activated in the sites.…”
mentioning
confidence: 97%
See 3 more Smart Citations
“…9,10 The results of our microRaman scattering measurements clearly showed the presence of boron ͑B͒ local vibrational peaks and Fano broadening of Si optical phonon peaks due to heavy B doping in SiNWs. 9 ESR measurements at 4.2 K showed the ESR signal of conduction electrons in phosphorus ͑P͒-doped SiNWs. 10 These results clearly proved that B and P atoms were doped in the crystalline Si core of SiNWs and were electrically activated in the sites.…”
mentioning
confidence: 97%
“…9,10 The study showed the states of dopant atoms in SiNWs such as bonding structures, sites, and electrical activities using micro-Raman scattering and electron spin resonance ͑ESR͒. 9,10 The results of our microRaman scattering measurements clearly showed the presence of boron ͑B͒ local vibrational peaks and Fano broadening of Si optical phonon peaks due to heavy B doping in SiNWs. 9 ESR measurements at 4.2 K showed the ESR signal of conduction electrons in phosphorus ͑P͒-doped SiNWs.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…SiNWs can be prepared via various methods, such as thermal evaporation [7], laser ablation [8], molecular beam epitaxy [9], and chemical vapor deposition (CVD) [10]. Plasma-enhanced chemical vapor deposition (PECVD) is one of the most important methods of SiNW preparation because it significantly reduces the deposition temperature and increases the growth rate of SiNWs [11,12].…”
Section: Introductionmentioning
confidence: 99%